2011
DOI: 10.1016/j.febslet.2011.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HIV siamycin I directly inhibits autophosphorylation activity of the bacterial FsrC quorum sensor and other ATP-dependent enzyme activities

Abstract: Edited by Richard Cogdell Keywords:Bacterial two-component signal transduction system FsrC Quorum sensing Siamycin I HIV inhibitor Enterococcus faecalis a b s t r a c t Siamycin I disrupts growth and quorum sensing in Enterococcus faecalis. Using purified intact protein, we demonstrate here that quorum membrane sensor kinase FsrC is a direct target of siamycin I, reducing pheromone-stimulated autophosphorylation activity by up to 91%. Inhibition was noncompetitive with ATP as substrate. Other ATP-binding enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 28 publications
1
37
0
Order By: Relevance
“…In a noncompetitive way siamycin I inhibits the autophosphorylation of membrane sensor kinases in Enterococcus faecalis (33). Sensor kinases are members of two-component systems, which were discovered in prokaryotes and later found in some eukaryotes, but not in the animal kingdom.…”
Section: Discussionmentioning
confidence: 99%
“…In a noncompetitive way siamycin I inhibits the autophosphorylation of membrane sensor kinases in Enterococcus faecalis (33). Sensor kinases are members of two-component systems, which were discovered in prokaryotes and later found in some eukaryotes, but not in the animal kingdom.…”
Section: Discussionmentioning
confidence: 99%
“…Siamycin I, a peptide effective against HIV fusion with human T cells, attenuates the ability of GBAP to activate FsrC and gelatinase production in E. faecalis , but its effects on other LytTR family members has not yet been ascertained [198,199]. Moreover, it is toxic for Enterococcus at doses sufficient for fsr inhibition.…”
Section: Targeting Agr and Analogues To Inhibit Diseasementioning
confidence: 99%
“…The highly constrained lasso structure of this compound (16e21 amino acids in length, with an N-terminal cyclized ring and a C-terminal tail that share a slipknot-like structure) is extremely resistant to thermal, chemical, and proteolytic degradation [41]. Siamycin I has been shown to directly inhibit the autophosphorylation activity of the FsrC quorum sensor of Enterococcus faecalis [42]. Synchrotron radiation circular spectroscopy revealed that the binding of siamycin I to FsrC exerts a significant effect on the local tertiary structures of the TyR and Trp resides of the protein and/or peptide ligands (gelatinase biosynthesis-activating pheromone) and siamycin I [43].…”
Section: Discussionmentioning
confidence: 99%